Uganda : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report, 2003)
Uganda showed strong macroeconomic stability, low inflation, and poverty reduction under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors commended the monetary and exchange rate policies, and stressed the need to strengthen fiscal sustainability and maintain a healthy financial sector. They emphasized the need to improve the infrastructure, expand financial intermediation, enhance governance to improve the investment climate, and encourage private sector-led investment and growth. They agreed that Uganda has successfully completed the first review under the PRGF Arrangement, and approved waiver.